2018
DOI: 10.1007/s41894-018-0021-9
|View full text |Cite|
|
Sign up to set email alerts
|

In-office tooth whitening

Abstract: Peroxides have been used to whiten teeth for over 100 years and among all whitening therapies the oldest is in-office bleaching. In this article, we will present the summary of the step-by-step procedure and side effects of this bleaching. Some comments regarding the number of clinical appointments for teeth whitening, concentration of the bleaching products, the effects of dentin dehydration and demineralization on the final outcome as well as bleaching-induced tooth sensitivity are given. At the end, some re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 7 publications
0
11
1
Order By: Relevance
“…Damage to soft tissues from tooth whitening can be minimized under the supervision of a dentist with a rubber dam. 154 However, preventing the exposure of soft tissues to whitening agents is difficult at home. Several studies have reported the side effects of whitening agents on soft tissues.…”
Section: Soft Tissuesmentioning
confidence: 99%
“…Damage to soft tissues from tooth whitening can be minimized under the supervision of a dentist with a rubber dam. 154 However, preventing the exposure of soft tissues to whitening agents is difficult at home. Several studies have reported the side effects of whitening agents on soft tissues.…”
Section: Soft Tissuesmentioning
confidence: 99%
“…Different tooth bleaching techniques on vital teeth performed or supervised by the dentist are described in the literature in search of color change 5–8 . Among them, the most established is the in‐office bleaching which uses higher concentrations of hydrogen peroxide (HP) (up to 40%), 9–13 the gel application being performed by the dentist, 14 and the at‐home bleaching, which uses lower concentrations of HP (up to 10%), performed by the patient himself with the application of bleaching gel in custom trays 15 . However, both techniques showed adverse effects and tooth sensitivity induced by bleaching was among the most prevalent 16 …”
Section: Introductionmentioning
confidence: 99%
“…bleaching which uses higher concentrations of hydrogen peroxide (HP) (up to 40%), [9][10][11][12][13] the gel application being performed by the dentist, 14 and the at-home bleaching, which uses lower concentrations of HP (up to 10%), performed by the patient himself with the application of bleaching gel in custom trays. 15 However, both techniques showed adverse effects and tooth sensitivity induced by bleaching was among the most prevalent.…”
mentioning
confidence: 99%
“…In‐office dental bleaching has become increasingly popular for its ability to deliver impressive tooth whitening results in a single session, 1 significantly improving patients' quality of life 2 . This technique involves using high concentrations of hydrogen peroxide, which are supplied in two separate vials that need to be mixed just before application 3,4 …”
Section: Introductionmentioning
confidence: 99%